Монголын улс төрийн намын санхүүжилтийн эрх зүйн зохицуулалтын тулгамдсан асуудал - С.МӨНХБАТ; Б.Эрдэнэдалай (Politology, 2023)
The issues of money and its effect on politics is increasingly gaining attention in the Mongolia in the same way as in other parts of the world. In fact, the experience Western democracies has shown the continuing difficulty of eliminating political corruption. However, in Mongolia there is an additional problem. Will the public there accept changes in their relations with elected representatives, for instance, ceasing to expect “gifts” for major family events, as part of the price of changes? This is especially a problem if the total amount available for subsides to political parties is based upon a multiple of the total population. Every taxpayer may feel that he or she is entitled to some return for his or her contribution, especially if politicians are suspected of having raked off disproportionate benefits for themselves. In that case the extreme pressures on political funding, often deteriorating into corruption, will continue. Without significant changes in public expectations, the problem of political corruption in Mongolia cannot be fundamentally addressed.